A Pastoral Counselor's Model for Wellness in the Workplace - Menz, Robert L, author.
1 online resource (174 pages)
Keywords: From the author: If this information helps the professional caregiver, it will help the employee; if it helps the employee, it will help the company! A Pastoral Counselor's Model for Wellness in the Workplace: Psychergonomics takes the concept of ergonomics beyond physical and environmental concerns to include a holistic interconnectedness of mind, body, and spirit. This unique book examines how psychosocial factors like family, conflict, emotional stress, addiction, and financial pressures can impact an employee's health and well-being. It incorporates a new paradigm of health care into wellness in the corporate setting, adding a new dimension to human health and safety. A Pastoral Counselor's Model for Wellness in the Workplace explores the workplace reality that illness and injury are not just the result of simple linear causes. Companies have data to determine how much they spend on insurance and worker's compensation claims but no way to measure the effects absenteeism, productivity, quality of work, and employee morale have on operating expenses. Using a holistic model of understanding, employers may now consider that an injury may be the result of an employee's depression, an accident might be caused by substance abuse, and an illness could be brought on by being worried sick. A Pastoral Counselor's Model for Wellness in the Workplace examines how employeesand employerscan be affected by: money troubles marriage problems depression grief stress conflicts addictions alcoholism anger A Pastoral Counselor's Model for Wellness in the Workplace: Psychergonomics is an essential resource for all helping professions, particularly in the areas of mental health and addiction. The book is an invaluable tool for pastoral counselors, chaplains, human resources managers, employee assistance professionals, psychotherapists, health care professionals, and educators.